Are Digital Methods Sufficiently Successful in Colour Determination for Monolithic All-Ceramic Crowns? - Vavřičková, Lenka; Kapitán, Martin; Wurfel, Eliška Charlotte (Acta medica (Hradec Kralove), 2022)
OBJECTIVE: The aim of this study was to compare the visual assessment of tooth shade with the measurement using intraoral scanner (IOS) and spectrophotometer devices. METHODOLOGY: The colour for a single unit implant supported crown was measured visually, using IOS, and spectrophotometer. The results of the digital methods were compared with the visual measurement. RESULTS: A complete colour match with the visual measurement was in 42.9% of cases for IOS, and in 33.3% of cases for spectrophotometry. The match in the colour value, hue, and chroma were in 61.9%, 95.2%, and 66.7% of cases, respectively, for the IOS; and in 61.9%, 61.9%, and 66.7% of cases, respectively, for the spectrophotometry. The differences between the IOS and spectrophotometry were not statistically significant. CONCLUSIONS: The most reliable method for tooth colour selection is the visual measurement by an experienced dentist. IOS and spectrophotometer can be used as an alternative method, however in both cases they should be verified using visual measurement.
Keywords: Spectrophotometry; spektrofotometrie; spectrophotometer; Color; vnímání barev; barvení protéz; colour match; intraoral scanner; Ceramics; Prosthesis Coloring; visual match; keramika; Color Perception; barva